О путях отбора слов для учебного двуязычного словаря - Песарскас, Б. (Kalbotyra, 1978)
To our knowledge the question of selecting entries for the learner’s dictionary of the type “native language – foreign language” has not been an object of investigation. The technique of their selection differs from the selection of foreign words for teaching purposes. Lithuanian words for the learner’s Lithuanian – English dictionary were chosen on the basis of English lexical minimums in accordance with the principle of semantic equivalence. To select words according to particular subjects and situations, set by the current Programme of Lithuanian secondary schools, a special experiment was carried out. Besides the experience of compiling Lithuanian – foreign language school dictionaries was made use of.